Disgenesia gonadal - Eibenschutz, C.; Mateo de Acosta, O.; Güell, J.R.; Pereira, R.; Egües, C. (Revista Cubana de Pediatría, 2023)
Estudio realizado en el Instituto de Endocrinologia en 28 casos durante 3 años